Survival Kinetics of Vibrio Species in a Tropical Estuary along the Southwest coast of India - as a function of selected Environmental Factors - Silvester, Reshma; C. Antony, Ally; Yousuf, Jesmi; Madhavan, Ajin; Sooria, P. M.; Kokkat, Aswin; Harikrishnan, M.; Hatha, Mohamed (Fishery Technology, 2021)
Vibrio species, autochthonous to aquatic environments worldwide, comprises of various species causing serious infections in humans and aquatic animals. Studying the survival ability of pathogenic Vibrio spp. in the aquatic environments is significant to identify the risk posed by them to aquatic animals as well as the recreational users of the system. However, in spite of their public health significance, the removal kinetics of this organism are not studied in detail from Cochin estuary, a highly productive estuarine system along the south-west coast of India. Here we aim to study the survival kinetics of pathogenic Vibrio spp. (V. parahaemolyticus, V. mimicus, V. proteolyticus, V. alginolyticus and V. vulnificus) in the estuary as a function of biological and physicochemical factors based on microcosm experiments. All the five Vibrio spp. showed prolonged and better survival in the estuarine sediment compared to water. This indicates that the sediments of Cochin estuary may act as permanent repository of this bacterium and is a matter of serious concern. Biological factors and chemical composition of estuarine water revealed to play a significant role in the removal of Vibrios from the estuarine environment. Exposure to sunlight also exhibited deleterious effect on the survival of these organisms. Thus, our overall findings reveal that the estuarine system has a self-purifying capacity to control the pathogens such as Vibrio. However, entry of high load of pathogens into the system through pollution and anthropogenic activities may disrupt this balance.